A mantle length structured stock assessment model for the jumbo squid, Dosidicus gigas, fishery of the Ecuadorian Pacific: a limited data approach. Issue 4 (21st April 2017) - Morales-Bojórquez, Enrique; Pacheco-Bedoya, José Luis
ABSTRACT: The jumbo squid Dosidicus gigas is a new fishery resource in Ecuador; the species is harvested from January to December every year. Biological sampling was carried out each month during March–December (2013) and January–December (2014) in different coastal zones off Ecuador, and the monthly mantle length (ML) composition was obtained from field data in the coastal areas. The catch-at-mantle length data were analysed based on the mantle length structured model (CAMLA). The results showed that the biomass of D. gigas in Pacific Ecuadorian waters was 641, 915 t (2013) and 1, 866, 857 t (2014). For 2013, for squid smaller than 30 cm ML the biomass was greater than 30, 000 t, while individuals between 35 and 48 cm ML had an estimated biomass varying between 35, 000 and 45, 000 t. During 2014, the biomass estimated for squid smaller than 30 cm ML was low (40, 000 t or less); however, squid between 38 and 48 cm ML showed a change in biomass compared with the previous fishing season, varying from 100, 000 to 190, 000 t. The harvested rate-at-mantle length for squid larger than 35 cm ML was higher than for individuals between 12 and 30 cm ML. The CAMLA model was found to be appropriate for modelling catch-at-mantle length of jumbo squid in Ecuadorian waters, and the model can be used to obtain harvest management quantities, as well as quantitative outputs useful for Ecuadorian stakeholders.